Heat transfer distribution of impinging flame and air jets – A comparative study. (5th January 2016) - Kadam, Anil R.; Tajik, Abdul Raouf; Hindasageri, Vijaykumar
Highlights: Heat transfer distributions of impinging air and flame jets are compared. The Nusselt number distributions are comparable with some deviations. CFD simulation is done to understand the jet spreading and its effect on heat transfer. A scale analysis is carried out to understand the effect of various forces. Abstract: Heat transfer distribution of impinging flame jet is compared with that of the impinging air jet based on the experimental data reported in literature for methane-air flame jet and air jet impingement for Reynolds number, Re  = 600–1400 and the non-dimensional nozzle tip to impingement plate distance, Z/d  = 2–6. The comparative data based on mapping experimental data reported in literature suggest that there is a good agreement between the Nusselt numbers for higher Z /d near stagnation region. However, away from the stagnation region, the Nusselt number for flame jet is higher than that of air jet for similar operating conditions of Re and Z/d . A CFD simulation for impinging air jet and impinging flame jet is carried out to explain the physics and reason for the deviations observed in experimental data. A scale analysis is carried out to identify the dominant forces and their influence on the heat transfer distribution on the impingement plate.